Out-of-core simplification with appearance preservation for computer game applications - 313299 Tan, Kim Heok (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2006